Activating Istisna'a in Islamic banks to finance housing for people with limited income - the case of Jordan - Alhoul, Mohyi Aldin Abu; AL-Zghoul, Mohammed Hussein; AlAli, Shireen Mahmoud; Alomari, Khalid Faris (Asian Economic and Financial Review, 2023)
This study aims to demonstrate the effectiveness of an Istisna’a contract in financing the housing sector for low-income people in Jordan and attempts to activate this formula in Islamic banks. The contribution to the provision of housing is considered a crucial social service. The study introduces Islamic financial banks and provides a definition of Istisna’a. A qualitative research method was used, collecting information from books, reports, journals, newspapers, and websites. The results of the study highlight the significant economic importance of the Istisna’a contract as a key driver of economic activity, including commercial, industrial, and agricultural sectors. The Istisna’a formula is regarded as one of the best banking methods that is compatible with supply contracts. While the survey results only reflect the study sample, there is a moderate potential to activate Istisna’a for financing low-income housing in Jordan through Jordanian Islamic banks. The study population comprises all 384 workers in Jordanian Islamic banks for the 2019 academic year.